Proceedings of the 2010 Workshop on Massive Data Analytics on the Cloud 2010
DOI: 10.1145/1779599.1779606
|View full text |Cite
|
Sign up to set email alerts
|

Efficient updates for a shared nothing analytics platform

Abstract: In this paper we describe a cloud-based data-warehouselike system especially targeted to time series data. Apart from the benefits that a distributed storage built on top of a shared-nothing architecture offers, our system is designed to efficiently cope with continuous, on-line updates of temporally ordered data without compromising the query throughput. Through a totally customizable process performing asynchronous aggregation of past records, we achieve significant gains in storage and update times compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Position papers have suggested a need for substantial work in this area (e.g., [14,15,16]). Individual efforts have made piecemeal advances, for 40 NICK CERCONE, F'IEEE example by migrating analytic applications to the cloud for time series data [17] and by devising data warehouses for the cloud [18]. There is interest in using the MapReduce paradigm for analytics (e.g., [19,20]); for example, IBM Research reported efforts primarily focused on extracting and analyzing large-scale unstructured data to do search-driven analytics us ing the Hadoop platform [21].…”
Section: 1mentioning
confidence: 99%
“…Position papers have suggested a need for substantial work in this area (e.g., [14,15,16]). Individual efforts have made piecemeal advances, for 40 NICK CERCONE, F'IEEE example by migrating analytic applications to the cloud for time series data [17] and by devising data warehouses for the cloud [18]. There is interest in using the MapReduce paradigm for analytics (e.g., [19,20]); for example, IBM Research reported efforts primarily focused on extracting and analyzing large-scale unstructured data to do search-driven analytics us ing the Hadoop platform [21].…”
Section: 1mentioning
confidence: 99%
“…Το Brown Dwarf [DTK10a,DTK10c,DTK10b] είναι ένα σύστημα το οποίο διανέμει μια κεντρική δομή δεικτοδότησης, το Dwarf [SDRK02] στους κόμβους ενός αδόμητου δικτύου "εν κινήσει" (on-the-y), επιταχύνοντας τόσο τη δημιουργία του όσο και την επίλυσης των ερωτημάτων χάρη στην παραλληλοποίηση που επιβάλλει. Τα ερωτήματα ανάλυσης καθώς και οι ενημερώσεις πραγματοποιούνται online μέσω των συνεργαζόμενων κόμβων του αδόμητου δικτύου επικάλυψης, εξαλείφοντας τη δαπανηρή συμβατική διαδικασία που συνήθως γίνεται ασύγχρονα.…”
Section: το σύστημα Brown Dwarfunclassified
“…Brown Dwarf [DTK10a,DTK10c,DTK10b] is a data analytics system that distributes multidimensional data over commodity network nodes, without the use of any proprietary tool.…”
Section: E Brown Dwarf Systemmentioning
confidence: 99%